"I Don't Want to Die in Here": Absence and Vulnerability in COVID-19 News Coverage of Prisons. (April 2023) - Schneeweis, Adina; Foss, Katherine A.
This research examines how news constructed vulnerability in the coverage of COVID-19 and populations in prisons and jails. Focused on key moments during the moral panic around the pandemic, the analysis of publications from across the U.S. found substantial reporting earlier in 2020, and a striking absence and ignorance of key developments later into 2021. Six news discourses - journalistic objectivity, blaming and abandonment, vulnerability, compassion, vilification, and absence - were complicated by the climate of demonstrations for racial justice.